Developing ai assistants, agents, and collaborative platforms - Bustillos Ortega, Olda (2025)
This article explores the development and application of artificial intelligence (AI) in the creation of assistants, agents, and collaborative platforms. Various applications and uses of AI are analyzed, highlighting their impact on education, industry, customer service, project management, and user experience. Three analogies are contrasted to describe and understand the application of AI in an organization: the Chef de Cuisine, the CMMI maturity model, and the Supply Chain. Methods and technologies for the development of these systems are examined, as well as technical challenges, risks, and ethical considerations in their implementation. Initiatives for AI assistants designed for university professors and AI agents in industrial processes are analyzed, exploring their functionalities and benefits. Figures and tables summarize the findings, and recommendations are provided for the implementation of AI Agents and Assistants in academia, institutions, and companies.